Age-Related Inflammation and Oxidative Stress in the Cochlea Are Exacerbated by Long-Term, Short-Duration Noise Stimulation - Fuentes-Santamaría, Verónica; Alvarado, Juan Carlos; Mellado, Susana; Melgar-Rojas, Pedro; Gabaldón-Ull, María Cruz; Cabanes-Sanchis, José J.; Juiz, José M. (Frontiers in Aging Neuroscience, 2022)
We have previously reported that young adult rats exposed to daily, short-duration noise for extended time periods, develop accelerated presbycusis starting at 6 months of age. Auditory aging is associated with progressive hearing loss, cell deterioration, dysregulation of the antioxidant defense system, and chronic inflammation, among others. To further characterize cellular and molecular mechanisms at the crossroads between noise and age-related hearing loss (ARHL), 3-month-old rats were exposed to a noise-accelerated presbycusis (NAP) protocol and tested at 6 and 16 months of age, using auditory brainstem responses, Real-Time Reverse Transcription-Quantitative PCR (RT-qPCR) and immunocytochemistry. Chronic noise-exposure leading to permanent auditory threshold shifts in 6-month-old rats, resulted in impaired sodium/potassium activity, degenerative changes in the lateral wall and spiral ganglion, increased lipid peroxidation, and sustained cochlear inflammation with advancing age. Additionally, at 6 months, noise-exposed rats showed significant increases in the gene expression of antioxidant enzymes (superoxide dismutase 1/2, glutathione peroxidase 1, and catalase) and inflammation-associated molecules [ionized calcium binding adaptor molecule 1, interleukin-1 beta (IL-1β), and tumor necrosis factor-alpha]. The levels of IL-1β were upregulated in the spiral ganglion and spiral ligament, particularly in type IV fibrocytes; these cells showed decreased levels of connective tissue growth factor and increased levels of 4-hydroxynonenal. These data provide functional, structural and molecular evidence that age-noise interaction contributes to exacerbating presbycusis in young rats by leading to progressive dysfunction and early degeneration of cochlear cells and structures. These findings contribute to a better understanding of NAP etiopathogenesis, which is essential as it affects the life quality of young adults worldwide.